2019
DOI: 10.1111/are.13957
|View full text |Cite
|
Sign up to set email alerts
|

Sporophytic photosynthesis and gametophytic growth of the kelp Ecklonia stolonifera affected by ocean acidification and warming

Abstract: Juvenile sporophytes and gametophytes of Ecklonia stolonifera were incubated in combinations of three pCO 2 levels (360, 720 and 980 ppmv) and two temperatures (10 and 15°C for sporophytes; 15 and 20°C for gametophytes) to examine potential effects of climate change on photosynthesis and growth. Sporophytes had significantly higher maximum quantum yields (F v /F m ) and maximum relative electron transport rates (rETR max ) at 720 ppmv than 360 and 980 ppmv. Also, these parameters were significantly lower at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Some results showed that OA negatively influenced the microscopic development of Macrocystis pyrifera and Undaria pinnatifida (Gaitán-Espitia et al, 2014; Xu et al, 2015; Gao et al, 2019a), which may be due to the inhibition of cell activities (Ragazzola et al, 2012). In contrast, kelp sporophytes exhibited positive physiological responses to OA (Schmid, Mills & Dring, 1996; Olischlaeger et al, 2012; Gao et al, 2019a; Gao et al, 2019b) due to stimulation of photosynthetic activities by increased inorganic carbon (Olischlaeger et al, 2012). Additionally, kelp species benefit from an increase in nutrient availability in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Some results showed that OA negatively influenced the microscopic development of Macrocystis pyrifera and Undaria pinnatifida (Gaitán-Espitia et al, 2014; Xu et al, 2015; Gao et al, 2019a), which may be due to the inhibition of cell activities (Ragazzola et al, 2012). In contrast, kelp sporophytes exhibited positive physiological responses to OA (Schmid, Mills & Dring, 1996; Olischlaeger et al, 2012; Gao et al, 2019a; Gao et al, 2019b) due to stimulation of photosynthetic activities by increased inorganic carbon (Olischlaeger et al, 2012). Additionally, kelp species benefit from an increase in nutrient availability in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharina latissima and Laminaria solidungula ) 88 . However, we do not discard the possibility that this effect might differ across different kelp life stages depending on their physiological requirements and inorganic carbon physiology 63 , 89 , 90 .…”
Section: Discussionmentioning
confidence: 91%
“…Evidence suggests that climate warming can exacerbate the negative effects of acidification and pollutants. For instance, warming and acidification combine to inhibit gametophyte growth in Ecklonia stolonifera (Gao et al, 2019) and increase mortality of Macrocystis pyrifera zoospores (Gaitán-Espitia et al, 2014), while warming and copper pollution interact synergistically to decrease the size of Macrocystis pyrifera gametophytes (but do not affect Undaria pinnatifida gametophytes; Leal et al, 2018).…”
Section: Multiple S Tre Ssor S In K Elp Ecosys Temsmentioning
confidence: 99%
“…Evidence suggests that climate warming can exacerbate the negative effects of acidification and pollutants. For instance, warming and acidification combine to inhibit gametophyte growth in Ecklonia stolonifera (Gao et al, 2019 ) and increase mortality of Macrocystis pyrifera zoospores (Gaitán‐Espitia et al, 2014 ), while warming and copper pollution interact synergistically to decrease the size of Macrocystis pyrifera gametophytes (but do not affect Undaria pinnatifida gametophytes; Leal et al, 2018 ). Warming also exacerbates damage caused by elevated ultraviolet radiation on sporophyte formation causing reduced egg release in Saccharina latissima and Laminaria digitata (Müller et al, 2008 ) and decreases in the zoospore germination rate in Alaria marginata (Fredersdorf et al, 2009 ).…”
Section: Multiple Stressors In Kelp Ecosystemsmentioning
confidence: 99%